2017
DOI: 10.1080/15389588.2017.1300257
|View full text |Cite
|
Sign up to set email alerts
|

Injury mitigation estimates for an intersection driver assistance system in straight crossing path crashes in the United States

Abstract: Objective: Accounting for one fifth of all crashes and one sixth of all fatal crashes in the United States, intersection crashes are among the most frequent and fatal crash modes. Intersection advanced driver assistance systems (I-ADAS) are emerging vehicle-based active safety systems that aim to help drivers safely navigate intersections. The objective of this study was to estimate the number of crashes and number of vehicles with a seriously injured driver (Maximum Abbreviated Injury Scale [MAIS] 3+) that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…A diagram depicting an LTAP/OD crash is shown in Figure 1. Previous work investigated the crash and injury benefits of a hypothetical I-ADAS in straight crossing path (SCP) crashes (Scanlon et al 2017) using the same I-ADAS system. Sander (2017) computed intersection automatic emergency braking (AEB) benefits using a different system design with effectiveness estimates developed using the German In-Depth Accident Study crash data set.…”
Section: Introductionmentioning
confidence: 99%
“…A diagram depicting an LTAP/OD crash is shown in Figure 1. Previous work investigated the crash and injury benefits of a hypothetical I-ADAS in straight crossing path (SCP) crashes (Scanlon et al 2017) using the same I-ADAS system. Sander (2017) computed intersection automatic emergency braking (AEB) benefits using a different system design with effectiveness estimates developed using the German In-Depth Accident Study crash data set.…”
Section: Introductionmentioning
confidence: 99%
“…These predictions have since tapered to ‘optimistic' scenarios describing a 50% adoption rate and 35% market share by 2040 (Forsgren, 2018), while research studies have suggested highly‐automated vehicles to have a market share between 24%‐87% by 2045 (Bansal & Kockelman, 2017). A higher market share of CAVs will result in higher collision reductions and fewer collisions being realized (Bareiss et al, 2019; Scanlon et al, 2017), which we expect in turn to change to the shifted loss distributions outlined in Section 2. Regardless, a rapid introduction of these vehicles requires a significant buy‐in from low‐ and middle‐income motorists, who would need to spend significantly beyond their typical vehicle purchase to secure a vehicle with self‐driving capabilities (Litman, 2015).…”
Section: Temporality Of Risk Landscapementioning
confidence: 96%
“…The scenarios we present in Section 2 do not envision that single-loss event models will drastically change with a gradual introduction of ADAS-enabled (Level 2) and partiallyautomated (Level 3) vehicles. Although it is difficult to determine the exact mixture of automated levels on the road, a greater level of safety afforded by ADAS-enabled vehicles will ensure that many incidents will be avoided or mitigated (Bareiss et al, 2019;Scanlon et al, 2015Scanlon et al, , 2017. In addition, initial forays in to CAV-sharing mobility services will increase the number of deadheading vehicles, decreasing occupancy rates on average.…”
Section: Implications For Insurer Pricing and Underwritingmentioning
confidence: 99%
See 1 more Smart Citation
“…Walking speed was estimated based on pedestrian age. Estimated walking speed ranged from 1.15 to 1.45 m/s (Gates et al 2006 The pedestrian AEB system braking peak magnitude was assumed to reach 0.8 g in dry road conditions, 0.4 g in wet road conditions, and 0.3 g in icy road conditions (Scanlon et al 2017). It was assumed that AEB would increase braking deceleration at a jerk of À30 m/s 3 (Lubbe and Kullgren 2015).…”
Section: Ttc ¼mentioning
confidence: 99%